Perception About One Minute Perceptorship In Postgraduate Training of Ophthalmology - Mir Ali Shah; S H Waqar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the perception of postgraduate trainees of ophthalmology about One Minute Preceptorship. Study Design: Mixed method study Place and Duration of Study: Department of Ophthalmology Peshawar Medical College, Peshawar from Jun 2020 to Dec 2020. Methodology: Ten post graduate FCPS trainees of Ophthalmology were included in this study. The participants were introduced to and practiced One Minute Preceptorship for a period of 01 month in the outpatient clinic. A questionnaire for study was filled anonymously after taking an informed consent, which included ten closed ended and three open ended questions to assess the efficacy of One Minute Preceptorship model in improving practical skills like focused history taking, case presentation, clinical diagnosis and devising an effective management plan. Results: One Minute Preceptorship model is an effective learning and teaching tool for improving case presentation skills (90%), identifying disease presentation (70 %), clinical diagnosis (60%), identification of risk factors (80%) and understanding the management plan (70%).Qualitative analysis of One Minute Preceptorship model usage showed improved clinical evaluation skills, more efficient time consumption, prompt clinical diagnosis and provision of self-reflection to the learner. Conclusion: OMP model can be employed as an effective learning and teaching tool in an outpatient clinical setting in postgraduate Ophthalmology training.